PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Andri Kurniawan; Fahmi Kamal; Muhammad Aziz Winardi; Devy Sofyanty (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The ultimate goal to be achieved by a company is to obtain the expected profit or profit in accordance with the specified target. Therefore, the factor of company size and profitability on firm value becomes interesting to study. The purpose of this study was to determine and analyze the effect of firm size and profitability both partially and simultaneously on firm value. This study recapitulates 9 issuers in the food and beverage subsector on the Indonesia Stock Exchange from 2016 to 2020. The data collected was processed using multiple regression with SPSS version 20. The results showed that company size has a positive and insignificant effect on firm value, profitability has an effect positive and significant to firm value, firm size and profitability simultaneously have a positive and significant effect on firm value.